Investigation on Void Effect on Shear Stress Field in Bonded Stepped-Lap Joint - Ghoddous,Behnam (2016)
Abstract In this paper, an adhesively-bonded stepped-lap joint suffering from a void within its adhesive layer is investigated. The void separates the layer into two sections. The joint is under tensile load and materials are isotropic and assumed to behave as linear elastic. Classical elasticity theory is used to determine shear stress distribution in the separated sections of adhesive layer along the overlap length. A set of differential equations was derived and solved by using appropriate boundary conditions. Finite element solution was used as the second method to verify the obtained results by analytical method. A two-dimensional model was created in ANSYS and meshed by PLANE elements. A good agreement was observed between two methods of solutions. Results revealed that the stepped-lap joint performed better in stress distribution with a void rather than single-lap and double-lap joints.